2017
DOI: 10.1007/s00167-017-4475-0
|View full text |Cite
|
Sign up to set email alerts
|

A prospective evaluation of proximal hamstring tendon avulsions: improved functional outcomes following surgical repair

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
58
0
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 29 publications
8
58
0
12
Order By: Relevance
“…While surgical repair for proximal hamstring ruptures in the acute setting has demonstrated good patient outcomes[5,12], reconstruction for chronic ruptures has been less favourable. In the chronic setting, particularly for patients complaining of significant functional impairment and large tendon defects, late-stage proximal hamstring reconstruction using a free graft harvested from the ipsilateral distal hamstrings demonstrated encouraging clinical outcomes out to 24 months.Albeit a small case series and underpowered to show statistical improvement, the subjective PHAT and SF-12 outcomes at 24 months post-surgery in the current series were similar to that reported previously for acute and chronic proximal hamstring repair[3]. Specifically in the evaluation of surgical reconstruction in the chronic setting using free grafts, Folsom et al[9] reported outcomes in five patients that underwent Achilles allograft reconstruction, and reported encouraging outcomes at final follow up (mean 20 months), albeit without reporting via any validated PROMs.…”
supporting
confidence: 86%
“…While surgical repair for proximal hamstring ruptures in the acute setting has demonstrated good patient outcomes[5,12], reconstruction for chronic ruptures has been less favourable. In the chronic setting, particularly for patients complaining of significant functional impairment and large tendon defects, late-stage proximal hamstring reconstruction using a free graft harvested from the ipsilateral distal hamstrings demonstrated encouraging clinical outcomes out to 24 months.Albeit a small case series and underpowered to show statistical improvement, the subjective PHAT and SF-12 outcomes at 24 months post-surgery in the current series were similar to that reported previously for acute and chronic proximal hamstring repair[3]. Specifically in the evaluation of surgical reconstruction in the chronic setting using free grafts, Folsom et al[9] reported outcomes in five patients that underwent Achilles allograft reconstruction, and reported encouraging outcomes at final follow up (mean 20 months), albeit without reporting via any validated PROMs.…”
supporting
confidence: 86%
“…In der vorliegenden Studie konnte gezeigt werden, dass die Gesamtergebnisse der Erhebung des PHAT-Scores ähnlich den Ergebnissen der bislang einzig vergleichbaren und zugrundeliegenden Studien von Blakeney et al [7,26] sind. In den dort durchgeführten prospektiven Erhebungen von insgesamt 72 [7] bzw.…”
Section: Diskussionunclassified
“…In den dort durchgeführten prospektiven Erhebungen von insgesamt 72 [7] bzw. 96 Patienten [26] ergab sich z. B. ein mittlerer PHAT-Score von 76,7 Pkt.…”
Section: Diskussionunclassified
See 2 more Smart Citations